The earliest history of the Christian gathering : origin, development and content of the Christian gathering in the first to third centuries - Alikin, Valeriy A. (Vigiliae Christianae, Supplements, 2010)
Recent research has made a strong case for the view that Early Christian communities, sociologically considered, functioned as voluntary religious associations. This is similar to the practice of many other cultic associations in the Greco-Roman world of the first century CE. Building upon this new approach, along with a critical interpretation of all available sources, this book discusses the social and religio-historical background of the weekly gatherings of Christians and presents a fresh reconstruction of how the weekly gathering originated and developed in both form and content. The topics studied here include the origins of the observance of Sunday as the weekly Christian feast-day, the shape and meaning of the weekly gatherings of the Christian communities, and the rise of customs such as preaching, praying, singing, and the reading of texts in these meetings.